Antithrombotic drugs, patient characteristics, and gastrointestinal bleeding: Clinical translation and areas of research. Issue 5 (September 2015) - Di Minno, Alessandro; Spadarella, Gaia; Prisco, Domenico; Scalera, Antonella; Ricciardi, Elena; Di Minno, Giovanni
Abstract Gastrointestinal bleeding (GIB) is a potentially fatal and avoidable medical condition that poses a burden on global health care costs. Current understanding of the roles of platelet activation and thrombin generation/activity in vascular medicine has led to the development of effective antithrombotic treatments. However, in parallel with a sustained coronary and cerebral flow patency, the increasingly intensive treatment with warfarin; direct oral anticoagulant drugs [DOACs], and/or with aspirin ± clopidogrel (or ± prasugrel or ± ticagrelor), has increased the burden of GIBs related to the use of antithrombotic agents. Compelling evidence concerning this issue is accumulating to indicate that: 1) the risk of GIB related to the use of antithrombotic drugs dramatically differs in different clinical settings; and 2) the characteristics of patients (e.g., severity of illness, comorbidities) in whom it is used exert a greater impact on the risk of GIB than the type of antithrombotic agent employed. The latter concept argues for the occurrence of GIB as reflecting the presence of patients at the highest risk for adverse outcomes. The HAS-BLED score identifies subjects at risk of bleeding among those untreated and those treated with warfarin, DOACs and/or low-dose aspirin. Its use within the frame of a severity score (e.g., the CHA2DS2-VASc score in patients with atrial fibrillation) helps balance the benefits and the risks of an antithrombotic treatment and identify those patients in whom the absolute gain (vascular events prevented) outweighs the risk of GIB. Potential implications of the latter information in settings other than atrial fibrillation is thoroughly discussed.